Health-related quality of life in patients with primary brain tumors during and three months after treatment with proton beam therapy. (March 2021) - Langegård, Ulrica; Fransson, Per; Bjork-Eriksson, Thomas; Johansson, Birgitta; Ohlsson-Nevo, Emma; Sjövall, Katarina; Ahlberg, Karin
Highlights: Acute symptoms were common after proton beam therapy among patients with brain tumors. HRQoL was equally distributed among patients with malignant and benign brain tumors three months after proton beam therapy. Clinically relevant changes were found in patients with malignant and benign brain tumors treated with proton beam therapy. Abstract: Background: Proton beam therapy (PBT) is increasingly administered to patients with primary brain tumors. Benefits of new treatments must be weighed against side effects and possible deterioration in health-related quality of life (HRQoL). The aim of this study was to describe and compare HRQoL, including acute symptom experiences and associated factors, in patients with malignant and benign brain tumors treated with PBT. Materials and Methods: Adult PBT-treated patients with primary brain tumors (n = 266) were studied. HRQoL was assessed with EORTC QLQ-C30, QLQ-BN20, HADS, ISI and MFI before, during and three months after treatment. Associations with demographic and medical factors were explored. Results: Between baseline and three months post-treatment: HRQoL decreased significantly in the global health/QOL domains physical functioning, role functioning and cognitive functioning in the malignant group, global health/QOL and physical functioning decreased significantly in the benign group, more comorbidity was significantly associated with increased motor dysfunction, leg weakness, headache and future uncertainty. Fatigue and depression were the most frequent symptoms in both groups. Independent predictors of risk factor recognition were age, sex, chemotherapy, comorbidity and education level. Discussion: Global health/QOL in patient with brain tumors is very complex and multidimensional. Symptoms are interrelated and related to patient, tumor and treatment factors. It is important to identify aspects of HRQoL that may be affected by treatment. These include both benefits, expected to improve HRQoL, and negative changes such as symptom experience and influencing factors. Evidence-based guidelines are needed for symptom management, and for high quality of care for patients experiencing low PBT-related HRQoL.